Evaluation of Indigenous Fruit Juices and Trap Colours for Managing Fruit Flies (Diptera: Tephritidae) in Butternut (Cucurbita moschata) - Sibanda, Mzobanzi; Musabayana, Zivanayi; Mathema, Ndabanye; Tembo, Lenon; Zanamwe, Pesanai; Mafirakureva, Tariro; Zhou, Mandhlenkosi; Moyo, Dean; Manjeru, Pepukai (University of Brawijaya, 2026)
Fruit fly is serious pest that reduce yield and fruit quality in Cucurbita moschata. Cucurbita moschata is an important food and cash crop. Development of eco-friendly strategies to reduce the effects of fruit fly damage is therefore important in ensuring global food security. The present study was carried out to evaluate the potential of combinations of trap colour and indigenous fruit juices, i.e., Sclerocarya birrea and Strychnos spinosa, to attract fruit flies to the traps. A field experiment was laid out as a 4 x 3 factorial design with three replicates of each of the 12 treatments arranged in a Randomized Complete Block Design. The first factor was the type of attractant and it consisted of four levels, i.e., Strychnos spinosa juice, Sclerocarya birrea juice, sugar and water. The second factor was trap colour and it consisted of three levels, viz., red, yellow and green. The number of fruit flies trapped was counted and classified into different fruit fly genera. The results showed that the number of fruit flies attracted by a combination of sugar and the three trap colours was statistically (P < 0.05) similar to number of fruit flies attracted by a combination of Strychnos spinosa juice and the three trap colours and a combination of Sclerocarya birrea juice and the three trap colours. Bactrocera spp has the highest number of flies trapped, with a grand mean of 39.9, followed by Ceratitis spp (15.5) and Drosophila melanogaster had the least number of flies trapped (9.94). It was concluded that Strychnos spinosa and Sclerocarya birrea juices can be used as alternative attractants to sugar for baiting and trapping fruit flies with traps painted yellow, green and red.